1996
DOI: 10.1128/mcb.16.5.2350
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein K Is a Transcription Factor

Abstract: The CT element is a positively acting homopyrimidine tract upstream of the c-myc gene to which the well-characterized transcription factor Sp1 and heterogeneous nuclear ribonucleoprotein (hnRNP) K, a less well-characterized protein associated with hnRNP complexes, have previously been shown to bind. The present work demonstrates that both of these molecules contribute to CT element-activated transcription in vitro. The pyrimidine-rich strand of the CT element both bound to hnRNP K and competitively inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
327
2
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(342 citation statements)
references
References 71 publications
10
327
2
3
Order By: Relevance
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…K protein is upregulated in malignant cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004), and it regulates the expression of genes involved in mitogenic responses, indicating that it has a direct role in cancerogenesis (Michelotti et al, 1995(Michelotti et al, , 1996Ostrowski et al, 2004). We have shown that following mitogenic stimulation, K protein is recruited to gene loci known to be upregulated in malignant states, including c-myc .…”
mentioning
confidence: 87%
“…As K protein is upregulated in tumour cells (Dejgaard et al, 1994;Mandal et al, 2001;Li et al, 2004) and modulates the expression of genes involved in mitogenic responses (Michelotti et al, 1995(Michelotti et al, , 1996Mandal et al, 2001;Ostrowski et al, 2004), altering its properties and introduction of a new phosphorylation site could make K protein either more or less conducive for the cellular processes that lead to tumorigenic state. If so, identification of this novel tumour-associated K protein isoform may prove to be a useful diagnostic, prognostic and/or therapeutic indicator.…”
Section: P<005mentioning
confidence: 99%
“…hnRNP proteins are involved in a variety of key cellular functions such as mRNA splicing [12], stabilization [13,14], nucleo-cytoplasmic transport [15 Á/17], and transcriptional control [18]. Some of them can also control the transcription of specific genes [19,20]. Several evidences, summarized in the following paragraph, support the hypothesis that the hnRNP proteins may be relevant in human carcinogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…Other hnRNP protein potentially relevant in tumorigenesis is hnRNP K. In the nucleus, this protein can bind directly to the promoter region of the human c-myc gene and functions as a transcription factor [19]. When localized to the cytoplasm, hnRNP K inhibits translation of specific mRNAs such as 15-lipoxygenase mRNA [36].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that some proteins, exempli®ed by hnRNPK (Michelotti et al, 1996) and the Drosophila transcription factor bicoid (Dubnau and Struhl, 1996;Rivera-Pomar et al, 1996), have the ability to act on both levels (Ladomery, 1997). Of particular relevance with respect to EWS/FLI is the ETS family protein PU.1.…”
mentioning
confidence: 99%